The Effect Of A Teaching Program Using The Six Thinking Hats in Learning Spiking In Volleyball for Physical Education & Sport Sciences College Students - Talib, Mohand (Journal of Physical Education, 2017)
The importance of the research lies in the integral role that colleges of physical education and sport sciences play in developing any society and educating its individuals through developing their mental and cognitive abilities. The aim of the research is to identify the effect of using six thinking hats in learning spiking in volleyball. The researcher used the experimental method. The subjects were (26) students from the college of Physical education and sport science/ university of Baghdad. The data was collected and treated using proper statistical methods. The researcher concluded that the teaching program plays a positive role in reorganizing the content of the teaching process as well as developing the thinking skills of students. Finally the researcher recommended using the six thinking hats as a principle of teaching process due to its great importance in solving problems that the students face while learning skills